PENGARUH GENDER, TEKANAN KETAATAN, PENGALAMAN AUDITOR, DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT (STUDI PADA KAP DI WILAYAH KOTA JAKARTA) - Sahbana Nuzulia Putri Dara; Nur DP Emrinaldi; Anggraini Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to determine the influence of gender, obedience pressure, auditor experience, andtime budget pressure on audit judgment (an empirical study at a firm in Jakarta). The researchmethod used is a quantitative research method. This study is a study that uses primary data. Thesampling technique in this study uses a purposive sampling technique. The population in this studyare auditors in the Jakarta area. The sample in this study amounted to 60. Data analysis wascarried out using SmartPLS4 software to process the data. Based on the results of the study, itshows that obedience pressure, auditor experience, have an effect on audit judgment while Genderand Time Budget Pressure do not have an effect on Audit Judgment in the Jakarta area.Keywords: Gender, Compliance Pressure, Auditor Experience, Time Budget Pressure and AuditJudgment